THE USAGE OF STYLISTIC TOOLS IN APHORISMS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
Aphorisms represent one of the most concise and expressive forms of language, encapsulating profound philosophical, moral, and social ideas within a limited linguistic framework. Their effectiveness largely depends on the use of stylistic tools that enhance memorability, emotional impact, and semantic depth. This article examines the role and functions of stylistic devices in aphorisms, focusing on metaphor, antithesis, paradox, irony, repetition, and parallelism. Through stylistic analysis, the study demonstrates how these tools contribute to the aesthetic value and pragmatic force of aphorisms, enabling them to function as powerful means of communication across cultures and historical periods.